Company valuation in thin markets: how does CAPM perform? - Holger Hinz; Sebastian Vollmer; Carsten Weimann (Journal of Applied Leadership and Management, 2012)
How does thin trading affect CAPMs valuation of a company? What are alternatives in case standard CAPM does not work?
Keywords: 650